Comparison of Stress and Deformation Distribution in Steel and Cobalt Chromium Materials for Femoral Bone Implants using Computational Biomechanics Analysis - hardiantati, hamizatul; Wulan, Widya Rachma; Timur, Fajar; Hasan, Nailul; Fauziyah, Nur Aini (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2025)
This study analyzes the mechanical performance of femoral bone implants using two types of materials, namely Alloys and Cobalt Chromium Alloys, as well as two variations in implant length (72 mm and 24 mm, and 80 mm and 20 mm). Simulation was conducted using the Finite Element Method (FEM) to evaluate mechanical parameters, such as directional deformation, equivalent stress, maximum principal stress, and minimum principal elastic strain. The analysis results show that the Cobalt Chromium Alloys material has smaller deformation compared to the Alloys, indicating better stiffness and load-bearing capacity. However, the maximum principal stress value is higher in Cobalt Chromium Alloys, indicating a greater risk of stress concentration. Meanwhile, a longer implant length shows a more even stress distribution compared to a shorter length. This study provides important insights into the influence of material and implant length on its mechanical performance, and can serve as a basis for designing optimal implants for specific medical needs